Potential of Native Rhizobia to Improve Cowpea Growth and Production in Semiarid Regions of Kenya - Nyaga, Julian Wanja; Njeru, Ezekiel Mugendi (Frontiers in Agronomy, 2020)
Cowpea (Vigna unguiculata (L.) Walp) is an important crop for smallholder farmers in marginal areas of sub-Saharan Africa. However, the crop growth and production are affected by low soil fertility due to poor soil management practices. Here, we assessed the effect of native and commercially available rhizobia inoculants on cowpea nodulation, growth and yields on three local cowpea genotypes (K-80, M-66 and KVU 27-1) in the semi-arid areas of Kenya. Field experiments were set in smallholder farms during the 2019 and 2020 cropping seasons. Native rhizobia were isolated from root nodules of cowpea plants used as trap cultures. The isolates were further assessed for symbiotic efficiency (SE) in the greenhouse and field experiments carried out during the short and long rains seasons. Field experiments were laid out in a randomized complete block design with three replications. The treatments consisted of the commercial inoculant (Biofix), native isolates, native + Biofix (consortium) and an uninoculated control. In the greenhouse, the native isolates significantly increased nodule number and dry weight (DW), shoot DW and root DW when compared to the uninoculated control. Additionally, 50% of the isolates recorded SE of >80%, while 35.7% and 14.3% of the isolates had SE of 51-80% and < 50% respectively. In the field, rhizobia inoculation significantly (P<0.05) increased nodulation and shoot dry weight (DW) compared to the uninoculated controls. Remarkably, rhizobia inoculation significantly increased yields where inoculation with native isolates recorded 22.7% increase in yield when compared to uninoculated control in the first season, and 28.6% increase in yield in the second season. However, the rhizobia inoculants did not show a preference for any of the cowpea genotypes and their performance was influenced by season and the study location. Our results demonstrate the existence of superior native isolates with potential to be developed to low-cost biofertilizer for sustainable cowpea production.